Distribution fitting for incomplete data - Ooi, Eileen Pei Shan. (2011)
This report reviews the effects of missing data on probability distributions which covers two main topics: (1) types of probability distributions and goodness-of-fit tests, and (2) missing data mechanisms and missing data techniques (MDT).